Navigating Challenges: Educational Interventions To Improve Nursing Students’ Understanding And Acceptance Of Artificial Intelligence (The Review of Diabetic Studies, 2025)
Background: The integration of Artificial Intelligence (AI) into healthcare education and practice marks a significant advancement. This study aimed to evaluate the effect of educational guidelines on nursing students' knowledge, attitudes, and barriers related to AI. Methods: A quasi-experimental design was utilized, involving a convenience sample of 600 undergraduate nursing students at Sohag University. Data was collected using three questionnaires: knowledge regarding AI, attitudes toward AI, and barriers hindering AI utilization. Pre- and post-intervention assessments were conducted. Results: The intervention resulted in a statistically significant improvement in knowledge (pre-test mean: 7.02 ± 0.78; post-test mean: 12.22 ± 1.56, p < 0.001) and attitudes (pre-test mean: 30.65 ± 2.04; post-test mean: 43.08 ± 1.78, p < 0.001). Barriers to AI use decreased from a mean of 7.03 ± 0.55 to 4.52 ± 1.43 (p < 0.001). A strong positive correlation was found between knowledge and attitudes (r = 0.657, p < 0.01). Conclusion: This study concluded that the educational guidelines had a significant effect on improving the studied undergraduate Nursing Students' knowledge, attitudes, and barriers hindering the use of artificial intelligence. Recommendations: The educational guidelines significantly enhanced nursing students' knowledge and attitudes towards AI while reducing perceived barriers. These findings underscore the necessity of incorporating AI training into nursing curricula to prepare future healthcare professionals for the evolving landscape of digital health.